1985
DOI: 10.1108/eb008278
|View full text |Cite
|
Sign up to set email alerts
|

A Empirical Study of the Differences Between Small Exporting and Non‐exporting Us Firms

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
2
11

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(96 citation statements)
references
References 19 publications
8
75
2
11
Order By: Relevance
“…This barrier was also found crucially in other studies (e.g. Cavusgil, 1984a;Diamantopoulos et al, 1990;Tesar & Tarleton, 1982;Yaprak, 1985).…”
Section: Inability To Contact Overseas Customers As the Classificatisupporting
confidence: 82%
See 1 more Smart Citation
“…This barrier was also found crucially in other studies (e.g. Cavusgil, 1984a;Diamantopoulos et al, 1990;Tesar & Tarleton, 1982;Yaprak, 1985).…”
Section: Inability To Contact Overseas Customers As the Classificatisupporting
confidence: 82%
“…Leonidou (1995b) also indicated that non-exporters tended to overemphasize EBs when compared to experienced exporters. Yaprak (1985) believed that non-exporters' perceptions on export challenges were based on a lack of knowledge of foreign markets, limited foreign market contacts, and personnel inexperience. In comparison, exporters are more likely to be familiar with external EBs, such as red tape, slow payment collection, and bad economic conditions in foreign markets.…”
Section: Export Experiencementioning
confidence: 99%
“…In consequence, relevant and timely information has often been regarded as an important factor in raising the confidence level of export-decision-makers in undertaking foreign marketing -across the whole range of activities (Yaprak, 1985). It is hoped that the findings of this study contribute (if not, just a little) in raising their confidence level of future as well as current exporters especially those in Malaysia as in guiding them to seek for information from the right sources.…”
Section: Discussionmentioning
confidence: 95%
“…Elles correspondent souvent aux barrières à l'exportation (Cavusgil, 1982 ;Bilkey et Tesar, 1977), aux caractéristiques démographiques de la PMI (Yaprak, 1985), aux caractéristiques managériales (Kleinschmidt et Cooper, 1984) et aux variables marketing (Cavusgil, 1982 ;Bilkey et Tesar, 1977). Ces variables n'ont qu'une relation positive ou négative, sans causalité explicite.…”
Section: Les Variables Accessoiresunclassified
“…-la seconde cherche à cerner les différences entre des PMI exportatrices et des PMI non exportatrices (Yaprak, 1985 ;Keng et Jiuan, 1989). …”
Section: Introductionunclassified